2020
DOI: 10.1186/s13018-020-02030-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the presence of the articular cartilage on the femoral component rotation in total knee arthroplasty in female and varus osteoarthritis knees

Abstract: Purpose Surgical techniques for total knee arthroplasty (TKA) require femoral rotational corrections that alter the position of the surface of the posterior femoral joint especially in kinematic alignment. However, preoperative planning of TKA based on computed tomography (CT), without knowing the femoral cartilage thickness, may cause post-surgery failures in femoral rotation. Therefore, this study aimed to evaluate the effects of posterior condyle cartilage thickness on rotational alignment in the femoral co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Koh et al indicated that the PCA was 2.2 ± 1.0° internally rotated relative to the sTEA through 3D bony and cartilaginous models based on MRI scans of end-stage osteoarthritis patients ( 13 ). Nam et al also reported that the PCA was 2.4 ± 0.9° with cartilage and 2.6 ± 1.0° without via femoral 3D MRI constructed models, and the variation was more evident in females, similar to our results ( 9 ). When performing femoral rotational resection, the same cutting angle leads to over 10% outliers, possibly resulting in malalignment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Koh et al indicated that the PCA was 2.2 ± 1.0° internally rotated relative to the sTEA through 3D bony and cartilaginous models based on MRI scans of end-stage osteoarthritis patients ( 13 ). Nam et al also reported that the PCA was 2.4 ± 0.9° with cartilage and 2.6 ± 1.0° without via femoral 3D MRI constructed models, and the variation was more evident in females, similar to our results ( 9 ). When performing femoral rotational resection, the same cutting angle leads to over 10% outliers, possibly resulting in malalignment.…”
Section: Discussionsupporting
confidence: 91%
“…We also evaluated the cartilage thickness in the distal and posterior femoral condyles and found no difference between the lateral and medial sides. Nam et al reported that the lateral posterior cartilage thickness (2.2 ± 1.0 mm) was significantly greater than the medial side (1.8 ± 0.4 mm), and Asada et al reported 1.5 ± 0.39 mm ( 9 , 10 ). However, both studies enrolled arthritic subjects where pathological cartilage wear or defects were expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various degrees of cartilage wear, osteophyte hyperplasia, and bone-end deformity may occur in different stages of knee osteoarthritis, and these changes may lead to the alteration of the position of femoral rotational reference axes ( 28 , 29 ). The posterior femoral condyles are in the load-bearing area of the femur, where cartilage wear is very common in patients with knee osteoarthritis, making the PCA susceptible to the deterioration of the knee joint circumstance ( 30 ). By analyzing more than 2,000 cases of femur CT data, Jang et al pointed out that, when compared with other rotational reference axes, the external rotation of the PCA by 3° was the most accurate reference to the sTEA, but it had the highest intersubject variability ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Residual cartilage in patients with osteoarthritis may affect the accuracy of the osteotomy. Nam et al proposed surgical planning for TKA based on CT does not consider articular cartilage and could lead to external malrotation of the femoral implant 13 .…”
Section: Discussionmentioning
confidence: 99%